Evaluasi Penyelenggaraan Surveilans COVID-19 di Puskesmas - Linda Zuliana; Haerawati Idris; Zulkarnain Zulkarnain (Journal of Telenursing (JOTING), 2022)
This study aims to evaluate the input of the puskesmas, including personnel resources (Head of City Health Office, Head of P2P Dinkes, Head of Health Center, COVID manager of Puskesmas, Puskesmas staff, COVID tracer, Community) facilities, funds and methods. The method used is descriptive qualitative. The results showed that the COVID-19 surveillance staff aspect was not appropriate for educational qualifications; the method used was following the guidebook such as the availability of prevention and evaluation guidelines, the available facilities/infrastructure in terms of quantity or quality, the communication tools were adequate and the equipment was out of stock medical use is also good, but PPE clothes are limited. The method for achieving the target of finding suspected COVID-19 is suitable. Funds used in the implementation of surveillance activities are sourced from APBD funds and the amount of the budget follows the needs, for funds for equipment are dropped from the health office. The implementation of case findings has been carried out according to procedures, and supervision of the increase in cases has also been carried out correctly. In conclusion, indicators of the success of implementing COVID-19 epidemiological surveillance at the Jambi City Health Center can be seen from the achievement of the set targets and the achievement of testing targets for case finding. The reason for not achieving the targets in testing and tracing according to informants' statements is because of many rejections in the Community. Keywords: COVID-19, Evaluation, Surveillance